1980
DOI: 10.1161/01.res.47.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of the nonworking and potassium chloride-arrested dog heart.

Abstract: SUMMARY In 21 dogs on cardiopulmonary bypass with ventricles kept empty, the mean beating but nonworking myocardial oxygen consumption (mVO 2 ) was 3.8 ml/min per 100 g at a heart rate of 158 beats/min. After subsequent potassium chloride arrest, the basal mVOs was 1.74 ml/min per 100 g. To compare these values with the working situation, we measured mVOj in these hearts before instituting bypass when the heart rate averaged 179 beats/min and arterial pressure averaged 108 mm Hg; mVOj was 9.2 ml/min per 100 g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 46 publications
(45 reference statements)
4
23
1
Order By: Relevance
“…During our ischemic protocol, the heart stops contracting in less than 1 min. Increased ATP depletion in TG hearts under this condition likely reflects increased ATP consumption for noncontractile function, predominantly for maintaining basal metabolism and ion homeostasis (33,34). On this note, we found a slower decline in pH i indicating a reduced accumulation of intracellular H ϩ in TG hearts.…”
Section: Table IIImentioning
confidence: 47%
See 1 more Smart Citation
“…During our ischemic protocol, the heart stops contracting in less than 1 min. Increased ATP depletion in TG hearts under this condition likely reflects increased ATP consumption for noncontractile function, predominantly for maintaining basal metabolism and ion homeostasis (33,34). On this note, we found a slower decline in pH i indicating a reduced accumulation of intracellular H ϩ in TG hearts.…”
Section: Table IIImentioning
confidence: 47%
“…; n ϭ 7-8 per group. myosin ATPase reaction (33,34). During our ischemic protocol, the heart stops contracting in less than 1 min.…”
Section: Table IIImentioning
confidence: 97%
“…Regression analysis of the relationship between cardiac work (assessed as PVA) and MV O 2 indicated that the decreased efficiency was not due to altered work-dependent MV O 2 (contractile efficiency) but rather to increased work-independent MV O 2 (unloaded MV O 2 ), expressed as an increase in the extrapolated value of the y-intercept of the regression line (26,29). Unloaded MV O 2 is the oxygen cost for nonmechanical work, consisting of the energy expenditure for BM and processes associated with EC coupling (20,48,50). The present study confirms, by direct measurement in mechanically unloaded hearts, that high FA exposure increases unloaded MV O 2 and is due not only to an increase in oxygen cost for BM but also to increased oxygen cost for EC coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, MV O2 measured under this condition is defined as the oxygen cost of basal metabolism (MV O2BM). The calculated difference between the measured unloaded MV O2 obtained in unloaded retrograde mode (MV O2unloaded) and MV O2BM was used to obtain the oxygen cost of EC coupling (MV O2ECC) (2,7,19,20).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation